MENELISIK DAMPAK PENGGUNAAN ENERGI TERBARUKAN PADA LAPORAN KEUANGAN - Gardina Aulin Nuha; Ari Sita Nastiti (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2020)
This study analyzed the impact of renewable energy in financial statement of energy companies listed on Indonesian Stock Exchange. This study used 3 energy companies during the 2018 period as samples. This study is written using a qualitative descriptive approach by analyzing the financial statements and annual reports of sample companies. Based on the data analysis, the results show that that the use of renewable energy had no particular impact on the financial statements of the energy sector companies. Information related to accounting treatment of renewable energy assets is still very minimal reported by the company. Especially for the companies that are still new to implementing and developing renewable energy, there is not much information related to renewable energy assets. This is indicated by the absence of accounting rules governing for the use of renewable energy, so that renewable energy assets are treated as the same as other fixed assets. Keywords: Accounting, Annual Report, Financial Statement, Fixed Asset, Renewable Energy